Academic Integrity Pledges -- Acculturating Students to Integrity within Canadian Higher Education - Miron, Jennie; Fenning, Krisstine (Canadian Perspectives on Academic Integrity, 2018)
Academic integrity, and its associated values, are an essential aspect of cultures that provide a foundation for conduct and behaviour of all members within higher education. Establishing such cultures support the quality of student learning as well as their ethical deportment within their programs of study. The merits of acculturating students within academic integrity has implications for their performance and commitment to similar conduct and behaviours in their chosen professional fields as positive, ethical, and caring professionals benefitting all who receive their care and service. Creating and sustaining such learning cultures requires a multifaceted approach and an understanding and appreciation for the complexity of nurturing such environments. Academic integrity pledges situated across the learning trajectory at meaningful times during students' developmental paths, serve as one strategy that can be effective to academic integrity efforts. How one School of Health Sciences has approached and realized academic integrity pledges are discussed, and may serve as an example for others. The successes and opportunities for future development are outlined and reviewed.